The effectiveness of laughter yoga yraining on guality of life and mental health of women with diabetes - Heidari , Elaheh; Shirazi , Mahmoud; Sanagouye Moharer , Gholamreza (Applied Family Therapy Journal (AFTJ), 2020)
Aim: This study aimed to determine the effectiveness of laughter yoga training on mental health and quality of life in women with diabetes. Method: The research method was quasi-experimental with experimental and control groups, pre-test design, post-test, and two-month follow-up. The statistical population was 70 people, female teachers with diabetes in schools of 1 and 2 regions of Education in Zahedan in 2018. These individuals were identified by sending a circular from the Ministry of Education, 60 of whom met the research’s inclusion and exclusion criteria. These 60 people were randomly divided into two groups of 30 experimental and control. Medical Laughter Yoga Program (2012) was performed on the experimental group members in 8 60-minute group sessions. The mental health and quality of life of both experimental and control groups were measured using the Goldenberg and Hiller (1978) General Health, and the quality of the life of Parkerson, Berhadot, and Tess (1990) questionnaires. Data were analyzed using repeated measures mixed analysis of variance test. Results: The results showed the effect of laughter yoga training on physical symptoms (F = 4.55, P = 0.037), anxiety symptoms and sleep disorders (F = 3.33, P = .024), social function (F =4.35, P = 0.041), depressive symptoms (F = 4.92, P = .030) and total mental health score (F = 3.68, P = .046) and total quality of life score (F = 6.63, P = .021) and the stability of this effect was in the follow-up stage. Conclusion: The findings show that laughter yoga affects increasing the mental health and quality of life of women with diabetes.